Bovine Lactoferrin Protects Dextran Sulfate Sodium Salt Mice Against Inflammation and Impairment of Colonic Epithelial Barrier by Regulating Gut Microbial Structure and Metabolites - Wang, Shalong; Zhou, Jingyu; Xiao, Da; Shu, Guoshun; Gu, Li (Frontiers in Nutrition, 2021)
Background: Ulcerative colitis is characterized by relapsing and remitting mucosal inflammation. Bovine lactoferrin (BL) is a multifunctional protein that could regulate the intestinal flora and has anti-inflammatory effects. The aim of this study was to investigate the therapeutic effect of BL on colitis. Methods: Dextran sulfate sodium salt (DSS) was utilized to establish a mouse model of colitis. BL was administered to treat DSS mice. The weight, the activity, and fecal status of the mice were recorded every day. Disease activity index was calculated. After the mice were euthanized, the colon length was measured. Hematoxylin and eosin staining was used to observe the pathological changes of the colon, and histological activity index was calculated. The myeloperoxidase (MPO) activity of colon tissue was measured. Western blot and immunohistochemistry were used to detect the expressions of Claudin-1, Occludin, and ZO-1. The expressions of IL-1β, IL-6, IL-10, TNF-α, and TGF-β in colon tissue were detected by ELISA. The protein expressions of MUC2, Reg3γ, β-defensin (HBD-2), and cAMP were detected by immunofluorescence (IF). 16S rDNA sequencing determined the type and structure of intestinal flora. Liquid chromatography–tandem mass spectrometry (LC-MS/MS) measured the metabolites of the intestinal flora. Results: Compared with the DSS group, the mice's weight in the BL group was higher and the length of the colon was longer. At the 14th day, MPO activity was higher in the BL group. The expressions of Claudin-1, Occludin, and ZO-1 in the colon were up-regulated in the BL group compared with the DSS group. The expressions of IL-1β, IL-6, and TNF-α were lower. The expressions of IL-10 and TGF-β were higher. IF showed that the expressions of MUC2 and β-defensin (HBD-2) were down-regulated, and the expressions of Reg3γ and cAMP were up-regulated. The 16S rDNA sequencing results showed that the alpha diversity and beta diversity were notably changed in the DSS mice treated with BL. Metabolomics results showed that BL changed purine metabolism in the DSS mice. Conclusion: BL alleviated colitis in mice by improving the inflammatory response and the structure of the colon barrier in the colon. BL changed the composition and metabolites of the intestinal flora. Thus, BL might be an effective nutritional supplement for colitis treatment.